INSTRUKSI BAHASA PEMROGRAMAN ADT (ABSTRACT DATA TYPE) PADA VIRUS DAN LOOP BATCH - Wahyudi, Jusuf; Berlian, Berlian; Rosdiana, Rosdiana (UNIVED Press, 2013)
Currently the software is found everywhere , not just on a supercomputer with 25 processors, a computer equipped with a p has software that can synchronize with a PC. Language used to instruct a computer programming language called . There are 2 types of programming languages consists of high-level languages and low-level languages . We know them: Basic, Algol, Cobol, Pascal, PL - 1, RPG, SNOBOL, APL, LISP, GPSs, ADA, DEAL and so that is a high -level language , machine language understood by the computer is the machine language instructions ( Machine language) which is a low-level language , high level language so that we mentioned above in order to be understood by a computer must first be translated by the compiler. From the results of research on Instructions Programming Language Programming Language That Uses the ADT (Abstract Data Type) On Virus And Loop Batch can be summed up in the current trend of virus that the average instruction looping using batch , which often interfere with computer performance,and theaddition of our unknown data working because thewindows aresetautomaticallyatstartupTask manager.